Mengungkap Persepsi Masyarakat tentang Pengalaman Layanan Kesehatan di Rumah Sakit Pemerintah Menggunakan Ulasan Online - Abdurrazak; Sukmana, Febrian Humaidi; Lalu Moh. Nazar Fajri; Sri Maryanti (Valid: Jurnal Ilmiah, 2024)
This research examines user reviews on Google Maps concerning the services of the Regional General Hospital (RSUD) in the West Nusa Tenggara Province (NTB). The research focuses on identifying rating patterns and predominant themes emerging within the reviews, as well as analyzing the differences in review length across different star ratings. Data were extracted from 112 reviews, ranging from 1 to 5 star ratings. A content analysis method was employed to categorize reviews based on themes and the assigned star ratings. Results indicate that reviews with 4 to 5 star ratings tend to be positive and elaborate on satisfying experiences, particularly in relation to friendly medical services and a comfortable environment. Conversely, low-rated reviews tend to be negative, primarily concerning poor services and inadequate facilities. The analysis of review length reveals significant variation among star ratings, with 1 star ratings yielding the longest reviews characterized by narratives abundant in disappointment and grievances. These findings underscore the significance of professional service and quality facilities in cultivating a positive user experience within hospital settings.